Development and Implementation of Study Board Media in Belief and Morals Learning at Madrasah Aliyah - Luthfi, Muhammad; Alauddin, Alauddin; Bungawati, Bungawati; M., Arwan (South Sulawesi Education Development (SSED), 2024)
This study aims to develop a study board as a learning media for the Belief and Morals subject for grade XII students at Madrasah Aliyah Batusitanduk. This research seeks to identify the study board's needs, design, validity, and practicality as a learning media. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The data were analyzed using qualitative and quantitative descriptive methods and collected through observation, interviews, and questionnaires. The results indicate that the study board media received a very valid rating from experts (90.8%) and was deemed highly practical by students (97.32%). These findings suggest that the study board effectively teaches beliefs and morals in grade XII.